2011
DOI: 10.1016/j.biomaterials.2011.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuities in the human bone–PDL–cementum complex

Abstract: A naturally graded interface due to functional demands can deviate toward a discontinuous interface, eventually decreasing the functional efficiency of a dynamic joint. It is this characteristic feature in a human fibrous joint i.e. bone-tooth complex that will be discussed through histochemistry, and site-specific high resolution microscopy, micro tomography, X-ray fluorescence imaging and wet nanoindentation techniques. Results demonstrated two causes for the occurrence of 5-50 μm narrowed PDL-space: 1) micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 46 publications
2
52
0
Order By: Relevance
“…Based on these large variations it is not surprising that the contacts between the bone and the tooth are in specific locations and not in others. Variations in PDL thickness have also been observed in bovine teeth (Bosshardt et al, 2008) and in humans (Hurng et al, 2011;Mandel et al, 1986;Toms et al, 2002b). We can therefore predict that their movements are also guided by contact areas.…”
Section: Discussionmentioning
confidence: 83%
“…Based on these large variations it is not surprising that the contacts between the bone and the tooth are in specific locations and not in others. Variations in PDL thickness have also been observed in bovine teeth (Bosshardt et al, 2008) and in humans (Hurng et al, 2011;Mandel et al, 1986;Toms et al, 2002b). We can therefore predict that their movements are also guided by contact areas.…”
Section: Discussionmentioning
confidence: 83%
“…Examples of entheses in the articulating musculoskeletal joints include, the ligament–bone and tendon–bone fibrocartilaginous interfaces (Benjamin & McGonagle, 2009). Within the oral and craniofacial systems, the ligament-alveolar bone and ligament–cementum fibrous interfaces of the dentoalveolar fibrous joint (Ho et al, 2010; Hurng et al, 2011; McCulloch, Lekic, & McKee, 2000) are responsible in part for the overall mechanics of fibrous joints. Because of the mismatch in elasticity at the ligament–cementum and cementum–dentin interfaces, from a pure engineering perspective strain concentrations should exist at the attachment sites and interfaces within load bearing joints (Ho et al, 2013; Qian et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…PGs have been identified within mineralized tissues as well as the mineral-free periodontal ligament (PDL) (Ababneh, Hall, & Embery, 1998; Ababneh, Hall, & Embery, 1999; Ho, Marshall, Ryder, & Marshall, 2007; Matheson, Larjava, & Hakkinen, 2005). PGs were also identified at the PDL–bone, PDL–cementum interfaces (Ho et al, 2010; Hurng et al, 2011; Lukinmaa, Mackie, & Thesleff, 1991). Previous studies from our laboratory have identified hygroscopic regions of the PDL–bone, PDL–cementum interfaces alluding to the presence of SLRPs (Ho et al, 2010; Hurng et al, 2011) and subsequently have identified SLRPs at the attachments sites (Chiu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a shift in homeostasis can cause modeling of the soft and hard structural elements (Giannobile et al, 2003), subsequently leading to an overall disturbance in organ biomechanics (Lee and Lin et al, 2013). Such shifts are often a result of perturbations (periodontal disease, parafunctional loads, and therapeutic load) to physiologic tooth mobility, which over prolonged loading can cause abnormal tooth displacement within the alveolar socket (Hurng et al, 2011). …”
Section: Introductionmentioning
confidence: 99%